PENGELOLAAN PENGGUNAAN PESTISIDA DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Nugrahini Susantinah Wisnujatia; Suwandi S. Sangadji (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
The use of pesticides in rice production has an impact on the environment. Pesticides are chemicals used to kill or control pests. The use of pesticides carries some risks, but farmers are used to using pesticides. However, the use of pesticides may lead to the contamination of groundwater. Therefore, the research question in this study was whether there any differences in rice production before and after pesticide reduction in Indonesia. This study aimed to analyze the difference between rice production before and after pesticide reduction in Indonesia. The secondary data in this study were rice production data from FAO. Data from 1968 to 1992 were data about rice production before reducing pesticide use in Indonesia, while data from 1993 to 2017 were data about rice production after reducing pesticide use in Indonesia. The applied data analysis was paired sample t-test using SPSS 25. The results indicated that there is a significant difference between rice production before and after reducing pesticide use in Indonesia.